Meningkatkan Hasil Belajar Matematika Materi Akar Pangkat Tiga Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Make A Match Pada Siswa Kelas V Semester Genap MIN 1 Sragen - Sri Rahayu, Okti; Nurjariah, Nurjariah; Nurlaila, Nurlaila (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the mathematics learning outcomes of cube root material using the Make A Match type cooperative learning model for grade V students. This type of research is a class action research conducted over two cycles. The subjects of this study were fifth grade students of MIN 1 Sragen, totaling 25 students consisting of 17 female students and 8 male students. The stages carried out include planning, action, observation, reflection. The research instruments used written tests and observation sheets. The analysis technique used was qualitative and quantitative data analysis. The results showed that there was an increase in learning outcomes by using the Make A Match type cooperative learning model on square root material. This can be seen from before the corrective action, the average student score was 58.8 with 24% completeness. In cycle I, the average student score increased to 72 with 68% completeness. In cycle II, the average student score was 81.2 and the completeness reached 92%. This shows that the use of the Make A Match learning model can improve student learning outcomes in the mathematics subject of cube root material in class V even semester of MIN 1 Sragen in the 2020/2021 academic year.